A escolha do professor padrão do Colégio Militar de Santa Maria e seus efeitos sobre professores: um estudo através das crenças - Prochnow, Ana Lucia Cheloti (2015)
The process of choosing the exemplary teacher in the Military School of Santa Maria aims to honor the teacher (civilian or military) who is outstanding among the others every school year. The choosing of this exemplary teacher occurs at two opportunities: first, the students in every grade individually and in secret vote for a teacher; later, the other teachers and school administrators choose, also in a secret vote, one of the seven names proposed by the students. This research aimed to analyze the process of choosing the exemplary teacher in the Military School of Santa Maria (CMSM), considering the effects on the other teachers through their beliefs. To do so, there was a description of the orientations for the pedagogical practice which are suggested by the System to understand the Military School of Santa Maria in terms of teachers work; it was built a profile of an exemplary teacher for teachers and students of the Military School of Santa Maria; and there was a compilation and an analysis of the beliefs of the teachers of the Military School of Santa Maria about the process of choosing the exemplary teacher. This research, which is built on a qualitative and quantitative model, is based on Vigotski (2007) and Barcelos (2001, 2004, 2006), who grant fundamental importance to the social interaction for the development of the individual; and also on Pimenta (2009), Mizukami (1986) and Cunha (1989), who approach topics related to the professional identity of the teacher, to the teaching approaches and to the profile of a good teacher . For the data collection, questionnaires given to students and CMSM teachers were used, as well as interviews with the teachers. The results showed that the students have their own criteria to choose a teacher, it can be affection or not, but mainly, they are related to the teacher s didactic work, and also showed that the other teachers choose because of affinity and empathy towards the workmate. It was perceived that the practice of choosing an exemplary teacher of CMSM affects positively the teachers, but mainly negatively the chosen ones as well as the ones not chosen as the exemplary teacher. Thus, it is believed that these negative effects can eventually be minimized, once the choosing process gets adjusted and discussed.